(untitled) (Architecture Image Studies, 2026)
The purpose of this study is to develop an assessment instrument for measuring the leadership skills of kindergarten teachers and to verify its validity and reliability using mathematical-statistical methods. Kindergarten teacher leadership skills consist of two main components: Core Competencies (Fundamental Skills): Abilities related to core leadership activities, such as planning, organizing, motivating, activating, and controlling. Personal Competencies (Individual Skills): Abilities based on personal traits, including decision-making, principled behavior, influence, advocacy, integration/unifying, and social communication skills. The development of the leadership assessment instrument was based on two dimensions: teacher leader characteristics and essential leadership competencies. For the purpose of evaluating these dimensions within the scope of this research, an assessment instrument was developed with 22 items: 13 questions related to leader characteristics and 9 questions related to essential competencies. The validity and reliability of this instrument will be assessed using Factor Analysis (Exploratory Factor Analysis and Confirmatory Factor Analysis). This study is expected to contribute to the development of a reliable instrument for assessing kindergarten teacher leadership.